2018
DOI: 10.1002/joc.5413
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prediction skill of Indian summer monsoon rainfall in NMME models and monsoon mission CFSv2

Abstract: Along with good prediction skill for major SST boundary forcings such as El Niño and IOD, their appropriate teleconnection spatial patterns also need to be captured well for the better prediction of the land precipitation like Indian summer monsoon rainfall. Here in the study, even though majority of the models has better skill for Nino3.4 index and IOD index, their spatial teleconnection pattern is higher for CFSv2‐T382 (pattern correlation of 0.8) and also has less bias in tropical region. Thus as seen in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 52 publications
3
40
0
Order By: Relevance
“…Even though CFSv2‐T126 well represents the convective centers over the ocean, a dry mean bias still persists same as in many coupled model Intercomparison Project Phase 5 and U.S. nation multimodel ensemble models over the central Indian region (George et al., 2016; B. B. Goswami et al., 2014; Pokhrel et al., 2013; Pillai et al., 2018; Ramu et al., 2016; Sabeerali et al., 2013; S. Saha et al., 2014; S. K. Saha et al., 2016). The dry bias over India is primarily attributed to the cold SST bias in the Indian Ocean (Figure 2b) and the presence of an anomalous anti‐cyclone over the central Indian region, thereby inhibiting the propagation of rain‐bearing monsoon low‐pressure systems over India (George et al., 2016; Srivastava et al., 2017).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Even though CFSv2‐T126 well represents the convective centers over the ocean, a dry mean bias still persists same as in many coupled model Intercomparison Project Phase 5 and U.S. nation multimodel ensemble models over the central Indian region (George et al., 2016; B. B. Goswami et al., 2014; Pokhrel et al., 2013; Pillai et al., 2018; Ramu et al., 2016; Sabeerali et al., 2013; S. Saha et al., 2014; S. K. Saha et al., 2016). The dry bias over India is primarily attributed to the cold SST bias in the Indian Ocean (Figure 2b) and the presence of an anomalous anti‐cyclone over the central Indian region, thereby inhibiting the propagation of rain‐bearing monsoon low‐pressure systems over India (George et al., 2016; Srivastava et al., 2017).…”
Section: Resultsmentioning
confidence: 85%
“…Generally, many global coupled models show wet bias in seasonal mean precipitation over oceans and dry bias over land regions (e.g., George et al., 2016; B. B. Goswami et al., 2014; Pillai et al., 2018; Ramu et al., 2016; S. K. Saha et al., 2013). Hence, it is imperative to develop techniques to reduce the systematic biases of CGCMs and provide information at smaller spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with observations, the ENSO–precipitation link is moderately (though weaker than in observations) reproduced in SEAS5 at Lead‐1 (Figure 10b), however, the teleconnection pattern weakens with an increase in lead time, which could be a reason for the decrease in forecast skill with an increase in lead time. Recent studies have reported an overly strong relationship between ENSO and the summer monsoon precipitation in different seasonal prediction systems (Pillai, Rao, Ramu, Pradhan, & George, 2018, among others). The ENSO–precipitation relationship in these studies may be exaggerated by use of the ensemble mean (not shown) instead of individual ensemble members.…”
Section: Resultsmentioning
confidence: 99%
“…The predictability of the coupled model at longer time scales sensibly lies in the fact that Ocean has better memory in virtue of its higher specific heat capacity. Nevertheless, the skill of the present coupled models is far less than the potential predictability limit of ISMR (Pillai et al, 2018). The National Centers for Environmental Prediction CFSv2 has been adapted for operational seasonal prediction of ISMR under National Monsoon Mission by the Government of India.…”
Section: Discussionmentioning
confidence: 99%